MITOS DAN PATRIARKI DALAM TRADISI ADAT BATAK DI FILM CATATAN HARIAN MENANTU SINTING: TELAAH SEMIOTIKA ROLAND BARTHES - Putri Vinalia Harahap; Vani Dias Adiprabowo (Lektur: Jurnal Ilmu Komunikasi, 2025)
The Batak ethnic group is known for upholding traditional customs and cultural values passed down through generations. Even in the modern era, many Batak communities continue to adhere to cultural norms and believe in various ancestral myths that shape their daily lives. This adherence often fosters patriarchal attitudes and leads to intergenerational tensions, particularly between parents and younger generations who adopt more modern perspectives. This study aims to analyze the representation of Batak customs in the film Catatan Harian Menantu Sinting by exploring its denotative, connotative, and mythological meanings through Roland Barthes’ semiotic framework. The research employs a qualitative descriptive method with content analysis techniques, supported by literature review and visual documentation focused on scenes that portray Batak cultural practices. The findings reveal that the film illustrates how Batak traditions—such as gender roles, the expectation of having male offspring, and prohibitions against interethnic marriage—are still observed in contemporary society. The film highlights generational conflicts that reflect shifting values and the challenges of maintaining traditional norms amidst societal change. Ultimately, the film serves as a cultural mirror that captures the tension between tradition and modernity in today’s Batak community.